Pengaruh Kompetensi Sumber Daya Manusia, Kinerja Manajerial Dan Job Relevant Information Terhadap Penerapan Anggaran Koperasi - Nyoman Sri Padmini; Made Konny Koswara; Gede Mandirta Tama (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to prove empirically: (1) the effect of human resource competence, (2) managerial performance and (3) job relevant information on the implementation of the cooperative budget implemented in Buleleng Regency, Bali. Descriptive quantitative method is one type of research applied in this study. The data sources used in this study used primary data in the form of questionnaires given directly to respondents. This research was conducted at cooperatives in Buleleng Regency with a total research sample of 74 cooperatives obtained from the Slovin formula. Tenik sampling based on Proportional cluster sampling and obtained the number of respondents in this study as many as 222 respondents. . The results of this study indicate that human resource competencies, managerial performance and job relevant information have a positive and significant effect on the implementation of the cooperative budget in Buleleng Regency, Bali Province.